Variation in Pb and Zn concentrations in different species of trees and shrubs and their organs depending on traffic density - Guney, Deniz; Koc, Ismail; Isinkaralar, Kaan; Erdem, Ramazan (Baltic Forestry, 2023)
Global population growth and increasing urban population density together are responsible for many disruptions such as environmental pollution, especially air one. Trace metals are of specific prominence as air pollutants because they are conservative pollutants. They tend to accumulate biologically; some have poisonous or carcinogenic effects, even at small concentrations. Among toxic trace metals, lead (Pb) and zinc (Zn) can be harmful to human health in certain quantities. These trace metals were included in primary pollutant lists of the Agency for Toxic Substances and Disease Registry. Therefore, determining these trace metal concentrations in the air and monitoring the differences is very important for determining the risky districts and the level of risk. Biomonitors are the most important indicators of differences in trace metal concentrations in the atmosphere. The plants chosen as biomonitors intake several of the trace metals from the soil and/or the air into their bodies and determining the level of this accumulation might provide insight into the trace metal pollution of the atmosphere and soil. The present study aims to determine the variations of Pb and Zn concentrations in various landscaping plants growing in different districts of Kastamonu (Türkiye) depending on tree species, organs and traffic density. It was found that unwashed leaves of Acer negundo L. can be suggested as a good biomonitor for the presence of both analysed trace metals. Keywords: biomonitor; air pollution; trace metal; lead; zinc; traffic
Keywords: traffic; lead; biomonitor; air pollution; zinc; Plants; trace metal; Pine; L.; Accumulation; 15. Life on land; 6. Clean water; 3. Good health; 13. Climate action; 11. Sustainability